2021
DOI: 10.3389/fnagi.2021.705097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anosognosia on Static and Dynamic Amplitudes of Low-Frequency Fluctuation in Mild Cognitive Impairment

Abstract: Background: Anosognosia is a significant symptom in patients with mild cognitive impairment (MCI) while the underlying neurological mechanism behind it is still unclear.Methods: A total of 121 subjects were included and classified into three groups, including 39 normal controls (NCs), 42 individuals with MCI without anosognosia (MCI-NA), and 40 individuals with MCI with anosognosia (MCI-A), based on their everyday cognition (ECog) questionnaire (discrepancy score). Resting-state functional MRIs were acquired f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous evidence of hippocampal atrophy combined with our results of decreased parahippocampal gyrus activity might account for and predict the cognitive impairment in PD patients. Similarly, in the study of vascular dementia and Alzheimer's disease, it was found that abnormal brain activities in different parts of brain were related to pathological processes, which provided theoretical support for explaining the mechanism of cognitive impairment in imaging perspective 52,53 . The study found that sharp ripples are a manifestation of interactions between the hippocampus and cortical loops, which are closely linked to cognition and memory 54 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous evidence of hippocampal atrophy combined with our results of decreased parahippocampal gyrus activity might account for and predict the cognitive impairment in PD patients. Similarly, in the study of vascular dementia and Alzheimer's disease, it was found that abnormal brain activities in different parts of brain were related to pathological processes, which provided theoretical support for explaining the mechanism of cognitive impairment in imaging perspective 52,53 . The study found that sharp ripples are a manifestation of interactions between the hippocampus and cortical loops, which are closely linked to cognition and memory 54 .…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, in the study of vascular dementia and Alzheimer's disease, it was found that abnormal brain activities in different parts of brain were related to pathological processes, which provided theoretical support for explaining the mechanism of cognitive impairment in imaging perspective. 52 , 53 The study found that sharp ripples are a manifestation of interactions between the hippocampus and cortical loops, which are closely linked to cognition and memory. 54 However, whether similar cognitive loop abnormalities exist in the PD co‐morbid cognitively impaired population warrants elucidation in terms of functional versus causal connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…A short window length may increase the risk of introducing spurious fluctuations in the observed dDC, and a long window length may hinder the characterization of the temporal variability dynamics of the dDC ( Zang et al, 2004 ). In line with our previous study ( Ge et al, 2022b ), we used a 50 TR (100 s) sliding window length and a 2 TR (4 s) step size ( Fu et al, 2021 ; Ge et al, 2022b ; Li et al, 2022 ; Sun et al, 2022 ). Based on the method similar to sDC, after calculating the DC of all voxels in the time window, each participant will obtain multiple window-based DC graphs.…”
Section: Methodsmentioning
confidence: 99%
“…The coefficient of variation (CV) map was computed across time windows. In order to be consistent with the previous dynamic rs-fMRI studies (35)(36)(37)(38), we used a 50 TR sliding window length and a 2 TR step length. We have further verified our results using 60 TR sliding window length and a 2 TR step size and added the figures for validation in the Supplementary Figures 1, 2.…”
Section: Estimation Of Static and Dynamic Functional Connectivitymentioning
confidence: 99%